2011
DOI: 10.3892/or.2011.1454
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid inhibits macrophage differentiation into the M2 phenotype and glioblastoma cell proliferation by suppressing the activation of STAT3

Abstract: Abstract. Tumor-associated macrophages (TAMs) polarized to the M2 phenotype promote tumor cell proliferation and are associated with a poor prognosis in patients with high grade glioma. We previously revealed that corosolic acid, a triterpenoid compound, inhibits the M2 polarization of human monocyte-derived macrophages (HMDM). In the present study, we examined whether oleanolic acid (OA), a triterpenoid compound whose structure is similar to corosolic acid, also shows inhibitory effects on M2 polarization in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Inhibition of macrophage differentiation to the M2 phenotype has been proposed to increase the tumor-associated immune response in patients with glioblastoma38. The findings of this study showed that treatment with CHA in glioma-bearing mice inhibited the distribution of M2 type macrophages (F4/80 + /CD206 + double labeled cells), consistent with the reduction of tumor weight observed in these mice.…”
Section: Discussionsupporting
confidence: 84%
“…Inhibition of macrophage differentiation to the M2 phenotype has been proposed to increase the tumor-associated immune response in patients with glioblastoma38. The findings of this study showed that treatment with CHA in glioma-bearing mice inhibited the distribution of M2 type macrophages (F4/80 + /CD206 + double labeled cells), consistent with the reduction of tumor weight observed in these mice.…”
Section: Discussionsupporting
confidence: 84%
“…Macrophages from STAT3 knockout mice release higher levels of pro-inflammatory cytokines [37]. Thus, STAT3 is regarded as one of the primary signaling molecules for macrophage polarization toward the M2 phenotype [38][41]. In this study, CSE treatment for 1.5 h exerted an apparent activating effect on the phosphorylation of JAK2 and STAT3 in macrophages.…”
Section: Discussionmentioning
confidence: 58%
“…Many factors contribute to the diversity of macrophage function, including the synergistic or antagonistic effects of different cells, cytokines, chemokines, protein kinases, hormones, TLR ligands, and complement and other endogenous molecules [25,26,27,28,29,30,31]. However, most Th1 and Th2 cytokines do not seem to induce a stable differentiation of macrophages into distinct subsets; they rather promote a transient functional pattern of responses that return to basal levels in a few (3-7) days [17].…”
Section: Discussionmentioning
confidence: 99%